Small business management system in agriculture of the Republic of Tyva - Kuular Sh.V.; Ondar A.V.; Sevek V.K.; Mongush A.K.-Ch; Sat U.V. (BIO Web of Conferences)
Small forms of entrepreneurship in agriculture play an important role in providing high-quality and environmentally friendly food, maintaining the proportion of the population in rural areas and a distinctive rural lifestyle. The purpose of the study is to develop the main directions for promoting the development and management of small forms of entrepreneurship in agriculture in the context of interaction between the federal, regional, and local levels of economic environment formation and its effective functioning. The object of the research is the management of small-scale farming in the agriculture of the region. The research subject is to improve the interaction of the management system of small business entities in the field of agribusiness in the Republic of Tuva. The authors proposed the organizational structure of the agricultural cluster of the Republic of Tyva. The practical significance of the study is related to the identification of problematic aspects in the agriculture of the region and the proposal of a management mechanism for the effective implementation of the priority national project “Technological food security”, which is aimed at creating conditions for sustainable production growth.